Manajemen Kurikulum Kulliyatul Mu’allimat Al-Islamiyah dalam Membentuk Akhlak Mulia Santriwati di Pondok Pesantren Mawaridussalam - Sari, Ana Harum; Lubis, Khairuddin; Zuliana, Eka (UIN Mahmud Yunus Batusangkar, 2025)
This type of research is descriptive qualitative research. Meanwhile, the approach taken by researchers in this research is to use a case study approach. For data collection techniques, researchers collect data through observation, interviews and documentation techniques. Meanwhile, to check and inspect data from various existing data collection techniques and data sources, researchers use data triangulation techniques. The research results that the researchers found were: (1) Kulliyatul Mu'allımat al-Islamiyah education management planning in forming noble morals for female students at the Mawaridussalam Islamic Boarding School is not only planning carried out to carry out Teaching and Learning Activities in the classroom, but also activities outside the classroom. including from the Kulliyatul Mu'allimat al-Islamiyah educational process which collaborates under the auspices of ustadz and ustadzah female student care staff. (2) Implementation of Kulliyatul Mu'allimat al-Islamıyah education management in forming the noble morals of female students inside and outside the classroom through the exemplary method (uswatun hasanah), the method of taking lessons (ibrah), the method of advice (mau'idzoh), and the method of training and habituation in everyday life to form noble morals among female students. (3) There are two types of education management evaluation process at the Mawaridussalam Islamic boarding school, namely for all female students at the Mawaridussalam Islamic boarding school and also evaluation for all teacher council that teaches.